Cognitive Reserve as a Protective Factor of Mental Health in Middle-Aged Adults Affected by Chronic Pain - Delgado-Gallén, Selma; Soler, M. Dolors; Albu, Sergiu; Pachón-García, Catherine; Alviárez-Schulze, Vanessa; Solana-Sánchez, Javier; Bartrés-Faz, David; Tormos, Josep M.; Pascual-Leone, Alvaro; Cattaneo, Gabriele (Frontiers in Psychology, 2021)
Chronic pain is associated with worse mental health and cognitive impairment, which can be a cause or a consequence of brain structure and function alterations, e.g., maladaptive plasticity, antinociceptive system dysregulation. Cognitive reserve reflects the effectiveness of the internal connections of the brain and it has been shown to be a protective factor in brain damage, slowing cognitive aging or reducing the risk of mental health disorders. The current study explored the impact of chronic pain on psychosocial factors, mental health, and cognition. Furthermore, we aimed to examine the role of cognitive reserve in the relationship between mental health and chronic pain clinical characteristics in middle-aged adults. The study group consisted of 477 volunteers from the Barcelona Brain Health Initiative who completed online surveys on pain, mental health, cognitive reserve, and psychosocial factors (sleep and quality of life). We described the differences in sociodemographic data, psychosocial factors, mental health, and self-perceived cognitive impairment, and neuropsychological assessment, between participants reporting pain compared with those without pain, as well as the main characteristics of the chronic pain group. Finally, to study the role of cognitive reserve in the modulation of the relationship between chronic pain and mental health, we compared variables between subgroups of participants with high/low pain intensity and cognitive reserve. The results showed that chronic pain was reported by 45.5% of middle-aged adults. Our results revealed that participants with chronic pain were older and had worse health status than people without pain. The presence of chronic pain affected working memory, mental health, and daily life activities. Moreover, cognitive reserve moderated the influence of pain intensity on mental health, resulting in less mental health affection in people suffering from high pain intensity with high cognitive reserve. In conclusion, the construct of the cognitive reserve could explain differential susceptibility between chronic pain and its mental health association and be a powerful tool in chronic pain assessment and treatment, principally due to its modifiable nature.